The Derivative Origin and its Impact on Directing the Qur'anic Connotation at Al-Taher Ibn Ashour–“ Kadhaya Almoshtakat - Rouag, Salim (Milev Journal of Research and Studies, 2022)
This research seeks to study one of the morphological issues in the language of the Noble Qur’an specifically, which is the issue of etymologyby addressing it in the field of exegesis, The one who investigates the writings of linguists and exegetes finds great interest in this aspect, since it is the return of words to their origins that reveals their connotations and meanings. Exegesis scholars have been interested in these principles by researching the subtle differences between synonymous words, or clarifying the semantic features of choosing a particular word in the Holy Qur’an, or putting a formula over another.What confirms the exegetes’ interest in the issue of derivation and research in the origins of words and their connotations is what we find in Ibn Ashour as a prominent model for those who gave their explanatory approach a linguistic tint. It is evident in his interpretation that he pays great attention to the origins of words and how to derive them when he returns most of the words to their origins and increases his interest in the relationship of derivation to semantics and meaningin view of the prevalence of attention to this morphological issue in this interpretation, this research, named "The Derivative Origin and its Impact on Directing the Qur'anic Connotation at Al-Taher Ibn Ashour–“ KadhayaAlmoshtakat” Derivative Issues as a Model", focused on analyzing some models related to this linguistic process and allocating them through its known types using the descriptive analytical approach, starting with a description of the important meanings and concepts contained in the research, followed by studying the examples that were extrapolated and discussed..